2017
DOI: 10.1097/ajp.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status and Opioid-related Problems and Concerns Among Men and Women on Chronic Opioid Therapy

Abstract: Objectives Smokers on chronic opioid therapy for non-cancer pain use prescription opioids at higher dosages and are at increased risk for opioid misuse and dependence relative to non-smokers. The current study aims to assess whether smoking is associated with problems and concerns with chronic opioid therapy from the perspective of the patient. Methods In a large sample (N = 972) of adult patients prescribed opioids for chronic noncancer pain, we examined sex-specific associations between smoking status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 47 publications
2
11
1
Order By: Relevance
“…Our finding that GpCO are more likely to be unemployed and work less is consistent with the multi-national questionnaire based study showing that the chronic use of opiates negatively influences the quality of life[ 41 ]. We found a higher prevalence of current smoking in GpCO, and a study by Young-Wolff et al[ 42 ] suggested a higher likelihood of opioid use disorder in current smokers vs non-smokers.…”
Section: Discussionsupporting
confidence: 71%
“…Our finding that GpCO are more likely to be unemployed and work less is consistent with the multi-national questionnaire based study showing that the chronic use of opiates negatively influences the quality of life[ 41 ]. We found a higher prevalence of current smoking in GpCO, and a study by Young-Wolff et al[ 42 ] suggested a higher likelihood of opioid use disorder in current smokers vs non-smokers.…”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, chronic nicotine exposure attenuated the analgesic effects of opioids, suggesting a cross-tolerance between opioids and nicotine. In humans, opioids and nicotine products (e.g., tobacco cigarettes) are commonly abused together and smoking status is an important predictor for using higher doses of prescription opioids and misuse of prescription opioids [127, 128]. Together, these studies suggest that ACh and opioids may play an important role in modulating the pharmacological effects of each other as well as impact ongoing use and addiction to opioids and nicotine.…”
Section: Interactions Between Opioids and Achmentioning
confidence: 99%
“…However, in Cryar's study, the MMEs, ranged between 250 to 5,540mgs compared to zero to 3,600mgs in the control group (23). In addition, other reports investigating the correlation between smoking and analgesic use during the first 12 hour postoperative period suggested that females, who underwent pelvic surgery and reported smoking, consumed ~20% more opioid drugs for controlling postoperative pain (13mg/12h versus 10.5mg/12h reported by controls) (24). In contrast, our findings suggest that there is not a statistical difference in total MMEs administered during the first 24 hour postoperative period between those with elevated circulating levels of catecholamines with no psychosocial issues, compared to controls with psychosocial issues, including; depression and history of nicotine and alcohol use.…”
Section: Discussionmentioning
confidence: 98%